The Diabetic Foot in a Multidisciplinary Team Setting. Number of Amputations below Ankle Level and Mortality - Wilbek, T. E.; Jansen, R. B.; Jørgensen, B.; Svendsen, O. L. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Aim: To describe the number of minor lower extremity amputations and mortality for diabetes patients treated by a specialized multidisciplinary foot care team.Methods: A retrospective descriptive study of medical records from patients with diabetes treated with minor amputations at the Copenhagen Wound Healing Center (CWHC) at Bispebjerg Hospital from 1996–2013.Results: 777 diabetes patients treated with minor amputations were included. 77% were males and 23% were females. 80% had T2 diabetes and 20% had T1 diabetes. 89% of the patients had a foot ulcer at first contact. There was a total of 1 231 minor amputations. The amputations were mainly trans-metatarsal amputations and partial amputations of toes. There was an increase in the number of minor amputations, but there was also an increase in the number of referred diabetes patients, thus the ratio of amputations per admitted diabetes patient was constant. Time from first amputation to death was 2.5 years. The 5-year mortality rate was 43% and 52% for T1 and T2 diabetes patients, respectively.Conclusion: Due to increased number of referred diabetes patients, the number of diabetes patients undergoing minor amputations increased over the years. Patients with diabetes, who underwent minor amputation, had a high mortality averaging 2.5 year to death; comparable to many types of cancer.
Keywords: diabetes; multidisciplinary foot care team; amputations; mortality